Knowledge and Attitudes about Breast Self-Examination (BSE) in Women of Childbearing Age (WCA) in Sigulang Village, Padangsidimpuan District - Dewi Aminasty Siregar; Elvi Suryani (PT Inovasi Pratama Internasional, 2022)
According to the World Health Organization (WHO) 8-9% of women will experience breast cancer, this makes breast cancer the most common type of cancer in women. The purpose of this study was to determine